Supplementation of dietary semen vaccariae extracts to lactating sow diets: effects on the production performance, milk components, and gene expression related to mammogenesis - Xu, Chaohua; Xie, Jiajun; Ji, Fengjie; Peng, Weiqi; Song, Yuzhuo; Diao, Xinping; Wu, Hongzhi (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the effects of dietary semen vaccariae extracts (SVE) on the production performance, colostrum components, and relative gene expression related to mammogenesis of lactating sows. 48 pregnant sows were selected and randomly allocated into four groups, with six replicates and two sows per replicate. The first group was the control (CON), while the other groups received the same diet further supplemented with 1.5, 3.0 and 4.5 g SVE per kg (SV1, SV2 and SV3, respectively). Compared with the control group, (1) the average daily gain was increased (P < 0.05) in SV1, SV2, and SV3 during the 11-21 days and 1-21 days of lactation; (2) the serum insulin-like growth factor-1, insulin, prolactin, and estrogen contents in SV1, SV2, and SV3 were increased (P < 0.05) on the 1st and 21st day of lactation; (3) The plasma Lysine, Threonine, and Tryptophan concentrations were also higher (P < 0.05) in SV1, SV2, and SV3 on the 1st and 21st day of lactation; (4) The milk Lysine, Methionine, Threonine, and Tryptophan concentrations were higher (P < 0.05) in SV1, SV2, and SV3 on the 1st and 21st day of lactation; (5) The milk lactose ratio and milk protein content were increased (P < 0.05) in the groups treated with semen vaccariae on the 1st day of lactation, while the milkfat ratio and milk protein content were increased (P < 0.05) in SV2 and SV3 on the 21st day of lactation; (6) the immunoglobulin M, A, and G contents were increased (P < 0.05) in the groups treated with the semen vaccariae on the first day of lactation; (7) the relative PRLR, STAT5a, FcRn, CSN2 and LALBA expressions were higher (P < 0.05) in the groups treated with the semen vaccariae on the 1st and 21st day of lactation. In this study, the optimum dosage was 3.0 g/kg semen vaccariae, which increased the average daily gain of piglets, total lactation yield, and serum hormone levels, improved the amino acid levels in plasma, and facilitated the milk quality, up-regulated the relative gene expressions in the mammogenesis.